BAGAIMANA FUNGSI KEPALA SEKOLAH DAN KOMUNIKASI INTERPERSONAL GURU TERHADAP MUTU PELAYANAN PENDIDIKAN? - Tasrikhah Tasrikhah (Edum Journal, 2020)
At present condition, education is a service. In order to satisfy users, the education service quality must be maintained to remain good. Factors that are strongly suspected of influencing educational services are the function of the principal and teacher interpersonal communication. Given the importance of education services, this study focuses on the function of principals and teacher interpersonal communication and their influence on the quality of education services. The method used is a survey method with a quantitative approach to 88 public elementary school teachers. Data processing techniques use both partial and multiple regression analysis. The results of the study show that: (1) There is a positive and significant influence between the implementation of the principal's function on the quality of education services (2) There is a positive and significant effect between teacher interpersonal communication on the quality of education services (3) There is a positive and significant influence between the implementation of the principal's functions and teacher interpersonal communication simultaneously on the quality of educational services. Starting from these conditions, the author suggests, that: (1) The quality of high education services is one of the missions that must be achieved by each school, the quality of education services has been shown to be influenced by the implementation of the principal's functions and teacher interpersonal communication. Therefore, principals should try to improve their function as school principals, especially those related to leading, managing and motivating with more optimal ways to explore their potential. So that it is expected that with optimal implementation of the principal's function, the quality of education services will increase. (2) Every teacher must develop himself by exploring his inner potential, participating in various trainings for teachers and continuing with higher education. In addition, in every self the teacher must try to instill awareness of the importance of maintaining interpersonal communication, for example by optimizing social media communication such as forming groups on Whatsapp, then education services at public elementary schools will be better and maintenance of friendship will be better.